Results of the WIRK prospective, non‐interventional observational study of recombinant activated factor VII (rFVIIa) in patients with congenital haemophilia with inhibitors and other bleeding disorders. (7th May 2013) - Birschmann, I.; Klamroth, R.; Eichler, H.; Schenk, J.; Kirchmaier, C. M.; Halimeh, S.
Summary: Recombinant activated factor VII (rFVIIa) has been available for the treatment of acute bleeding and for prevention of bleeding during surgery and invasive procedures in patients with congenital haemophilia with inhibitors (CHwI) and acquired haemophilia since 1996. The study objective was to assess the efficacy and safety of rFVIIa in patients with CHwI, acquired haemophilia, congenital FVII deficiency and Glanzmann's thrombasthenia, in a real‐life clinical setting. There were no specific inclusion or exclusion criteria; participation was offered to all German haemophilia centres known to use rFVIIa to treat patients with the above indications. Data on rFVIIa use and efficacy for the treatment of acute bleeding episodes and invasive procedures were recorded. Adverse drug reactions and recurrent bleeding episodes were also monitored. In total, 64 patients (50.0% women) received rFVIIa treatment. Patients experienced 281 evaluable bleeding episodes and underwent 44 invasive procedures. In 252 of 281 (89.7%) bleeding episodes, a stop (66.5%) or a significant reduction (23.1%) in bleeding was observed. No bleeding complications were reported for 42 of 44 (95.5%) invasive procedures covered with rFVIIa. A clear positive association was observed between early initiation of rFVIIa treatment for acute bleeding and efficacy. The total cumulative dose and number of injections were 468.3 ± 545.8 μg kg −1 and 3.6 ± 4.6 respectively. No drug‐related adverse events were reported. rFVIIa use in Germany provided effective haemostatic cover without associated adverse events in the management of acute bleeds and invasive procedures across a range of bleeding disorders.